Influence on the volumetric efficiency of friction displacement of polymeric material waste in a screw conveyor. - Синюк, О.М. (Problems of Tribology, 2016)
Synyuk O.M. Influence on the volumetric efficiency of friction displacement of polymeric material waste in a screw conveyor. The characteristics of the movement of the polymeric material in the grinding zone. The dependence of the effect of kinematic and dynamic parameters of the screw conveyor in the volumetric efficiency of transportation of the polymer material in the processing zone. The influence of the ratio of the friction coefficient between the polymer and the cylinder and between the polymer and the screw on the bulk material moving capacity. Recommendations to increase the volumetric efficiency of the polymer transport. Keywords: polymer, transportation, screw, material cylinder, processing, performance.